Chemical-based Maze Solving Techniques - Suzuno, Kohta; Ueyama, Daishin; Lagzi, István (Current Physical Chemistry, 2015)
Maze solving and finding the shortest path or all paths in a maze are interesting and challenging computational problems. These problems are important in robotics, urban transportation, and they provide model problems of network and graph theory. In the past decades, several unconventional computing methods have been proposed to solve a maze and to find its shortest path. In this review, we review the chemical-based methods proposed in the literature. In these methods, chemistry plays an important role in phenomena that drive maze solving.
Keywords: chemical waves